2008
DOI: 10.1891/0047-2220.39.1.28
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Participant and Service Characteristics on the Employment Outcomes of RSA Consumers with Visual Impairments: A Follow-up on Agency-Type

Abstract: As a follow up to previous studies, this article explores the role of personal and service characteristics and Vocational Rehabilitation (VR) agency type on the attainment of employment outcomes of persons with visual impairments. Results of the stepwise regression analysis indicated that the variables of age, education, and gender best predicted the employment outcomes of these consumers with visual impairments. Although statistically significant, agency type did not affect the income of VR consumers with vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…Several personal characteristics have predicted employment outcomes among VR consumers with sensory disabilities, including gender, race, ethnicity, age, and disability-related factors. Male gender was positively associated with employment outcomes across sensory disability groups (Bradley, Geyer, & Ebener, 2013; Cimera et al, 2015; Darensbourg, 2013; Estrada-Hernández, 2008; Giesen & Cavenaugh, 2012, 2013; Moore, 2002). Findings regarding race, ethnicity, and age have been less conclusive.…”
Section: Vocational Rehabilitation (Vr) Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Several personal characteristics have predicted employment outcomes among VR consumers with sensory disabilities, including gender, race, ethnicity, age, and disability-related factors. Male gender was positively associated with employment outcomes across sensory disability groups (Bradley, Geyer, & Ebener, 2013; Cimera et al, 2015; Darensbourg, 2013; Estrada-Hernández, 2008; Giesen & Cavenaugh, 2012, 2013; Moore, 2002). Findings regarding race, ethnicity, and age have been less conclusive.…”
Section: Vocational Rehabilitation (Vr) Researchmentioning
confidence: 99%
“…Hispanic ethnicity predicted positive outcomes for transition-age youth who are blind or visually impaired (Cimera et al, 2015; Giesen & Cavenaugh, 2012), but not for adults with visual impairments (Giesen & Cavenaugh, 2013; McDonnall, 2016) or consumers who are deaf or hard of hearing (Bradley et al, 2013). In some studies, younger age was associated with positive employment outcomes (Capella-McDonnall, 2001; Darensbourg, 2013; Estrada-Hernández, 2008; McDonnall, 2016), and older age was associated with positive outcomes in another (Dutta et al, 2008). Findings have been mixed regarding severity of hearing loss, with one study supporting higher odds of employment for consumers who are hard of hearing (Bradley et al, 2013) and another supporting higher employment rates for deaf consumers (Moore, 2001).…”
Section: Vocational Rehabilitation (Vr) Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to agency type, in 1997, the National Council on Disability recommended that separate vocational grants designate specific agencies to serve individuals who are visually impaired (Cavenaugh, Giesen, & Pierce, 2000). Numerous studies have indicated that agencies specifically designed to serve individuals with visual impairments have higher acceptance rates and rehabilitation rates (Cavenaugh et al, 2000;Estrada-Hernandez, 2008;Kitchner, 1982). A VR agency enters OOS when it does not have enough funding or resources to serve all applicants who may be eligible for services.…”
Section: Agency Characteristicsmentioning
confidence: 99%